2020
DOI: 10.1039/d0em00331j
|View full text |Cite
|
Sign up to set email alerts
|

Reductive transformations of dichloroacetamide safeners: effects of agrochemical co-formulants and iron oxide + manganese oxide binary-mineral systems

Abstract: Abiotic redox transformation rates of dichloroacetamide safeners slow when birnessite is added to slurries of Fe(ii)-amended hematite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Importantly, dichloroacetamide safeners can undergo photolysis (Kral et al, 2019;Su et al, 2019), hydrolysis (McFadden et al, 2022), abiotic reductive dechlorination (Ricko et al, 2020;Sivey & Roberts, 2012;Xu et al, 2020Xu et al, , 2022, and *Indicates significant difference compared with controls (shown as 0 for each figure). AD, AD-67.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, dichloroacetamide safeners can undergo photolysis (Kral et al, 2019;Su et al, 2019), hydrolysis (McFadden et al, 2022), abiotic reductive dechlorination (Ricko et al, 2020;Sivey & Roberts, 2012;Xu et al, 2020Xu et al, , 2022, and *Indicates significant difference compared with controls (shown as 0 for each figure). AD, AD-67.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, dichloroacetamide safeners can undergo photolysis (Kral et al, 2019; Su et al, 2019), hydrolysis (McFadden et al, 2022), abiotic reductive dechlorination (Ricko et al, 2020; Sivey & Roberts, 2012; Xu et al, 2020, 2022), and biotransformation (Abu‐Qare & Duncan, 2002) in the environment. These processes can result in the safener changing into structures like those of herbicides, which could be more toxic than the parent (Abu‐Qare & Duncan, 2002; Sivey & Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, abiotic reductive dechlorination of dichlormid and benoxacor can, respectively, yield the regulated herbicide allidochlor ( N , N -diallyl-2-chloroacetamide, commonly known as CDAA) and a known degradate, monochloro-benoxacor, which is toxic toward insect larvae. 7 , 8 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…The EPA has also identified AD-67 and furilazole as “likely to be carcinogenic to humans”. , Furthermore, some dichloroacetamide safeners, including dichlormid and benoxacor, can transform under environmentally relevant conditions to yield products with increased biological activity that may pose even greater risks to the environment and human health. For example, abiotic reductive dechlorination of dichlormid and benoxacor can, respectively, yield the regulated herbicide allidochlor ( N , N -diallyl-2-chloroacetamide, commonly known as CDAA) and a known degradate, monochloro-benoxacor, which is toxic toward insect larvae. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…2,3 As a result, birnessite-type manganese oxides play a significant role in controlling the cycles of several key nutrients as well as the fate and mobility of inorganic and organic contaminants. [4][5][6][7][8][9] Acid birnessite has been widely investigated because it is structurally similar to biogenic "natural" manganese oxides. [10][11][12][13] The birnessite reactivity is mainly affected by solution pH, surface properties and composition of MnO2 and structural characteristics of redox-active contaminants.…”
Section: Introductionmentioning
confidence: 99%